Some structural measures of API usability. (3rd September 2013) - Rama, Girish Maskeri; Kak, Avinash
SUMMARY In this age of collaborative software development, the importance of usable APIs is well recognized. There already exists a rich body of literature that addresses issues ranging from how to design usable APIs to assessing qualitatively the usability of a given API. However, there does not yet exist a set of general‐purpose metrics that can be pressed into service for a more quantitative assessment of API usability. The goal of this paper is to remedy this shortcoming in the literature. Our work presents a set of formulas that examine the API method declarations from the perspective of several commonly held beliefs regarding what makes APIs difficult to use. We validate the numerical characterizations of API usability as produced by our metrics through the APIs of several software systems. Copyright © 2013 John Wiley & Sons, Ltd.